A Business Ethics Experiential Learning Module: the Maryland Business School Experience - Loeb, Stephen E. (Teaching business ethics, 1997)
In this paper we describe the principal activities of the initial implementation in May of 1996 of one of the “Experiential Learning Modules (ELMs)” entitled “Business Ethics” (UMCP 1995, p. 7) that is part of the full-time MBA program at the College of Business and Management (Maryland Business School) of the University of Maryland at College Park (UMCP). Additionally, we briefly consider the location of this Business Ethics ELM in the curriculum of the Maryland Business School's full-time MBA program. We also outline how the Business Ethics ELM was developed. Further, we provide a discussion and a short conclusion.